2009
DOI: 10.1097/mcg.0b013e31819c392e
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Using Simvastatin in the Treatment of Nonalcoholic Steatohepatitis

Abstract: In this pilot trial, monotherapy with simvastatin does not seem to be an effective treatment for NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
158
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(177 citation statements)
references
References 41 publications
5
158
1
6
Order By: Relevance
“…[159][160][161][162][163][164][165][166][167] These studies consisted of small numbers of patients and have not been rigorously designed. A recent post-hoc analysis of the cardiovascular outcomes study, GREACE, 165 observed that statins significantly improve liver biochemistries and cardiovascular outcomes in patients with elevated liver enzymes likely due to NAFLD.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…[159][160][161][162][163][164][165][166][167] These studies consisted of small numbers of patients and have not been rigorously designed. A recent post-hoc analysis of the cardiovascular outcomes study, GREACE, 165 observed that statins significantly improve liver biochemistries and cardiovascular outcomes in patients with elevated liver enzymes likely due to NAFLD.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…Fig. 3) and radiological steatosis [53,54] in hyperlipidaemic NAFLD patients; in the only RCT with post-treatment histology, simvastatin had no effect on liver histology [56]. There was no significant publication bias (ESM Fig.…”
Section: Lipid-lowering Drugsmentioning
confidence: 99%
“…Ezetimibe Growing evidence connects non-esterified cholesterol accumulation in mitochondria to hepatocyte apoptosis, liver injury and NASH development [56][57][58][59][60][61]. On this basis, ezetimibe, a Niemann-Pick C1 like 1 protein inhibitor, was evaluated in two RCTs in NAFLD.…”
mentioning
confidence: 99%
“…2-4). 40 Trials in NAFLD. An RCT (quality score 8) randomized 186 hyperlipidemic NAFLD patients to 12 months of lifestyle advice plus atorvastatin, fenofibrate, or a combination of both (Table 1; Fig.…”
Section: Statinsmentioning
confidence: 99%